2002
DOI: 10.1002/hbm.10073
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the generators of the scalp recorded visuo‐verbal P300 using cortically constrained source localization

Abstract: Considerable ambiguity exists about the generators of the scalp recorded P300, despite a vast body of research employing a diverse range of methodologies. Previous investigations employing source localization techniques have been limited largely to equivalent current dipole models, with most studies identifying medial temporal and/or hippocampal sources, but providing little information about the contribution of other cortical regions to the generation of the scalp recorded P3. Event-related potentials (ERPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 186 publications
3
28
1
Order By: Relevance
“…Although previous fMRI results suggested that the target detection network is supramodal (Linden et al, 1999), recent fMRI and source localization findings (Ardekani et al, 2002;Kiehl and Liddle, 2003;Moores et al, 2003) and our present results indicate a modality-specific component, as evidenced by the IT contribution to the visual P3b. Previous intracranial EEG (iEEG) findings (Halgren et al, 1998), topographic scalp ERP studies (Johnson, 1989b;Falkenstein et al, 1994), and lesion studies (Johnson, 1989a) also indicated different sources for the visual and auditory modality.…”
Section: P3b and Sensory Modalitycontrasting
confidence: 94%
See 1 more Smart Citation
“…Although previous fMRI results suggested that the target detection network is supramodal (Linden et al, 1999), recent fMRI and source localization findings (Ardekani et al, 2002;Kiehl and Liddle, 2003;Moores et al, 2003) and our present results indicate a modality-specific component, as evidenced by the IT contribution to the visual P3b. Previous intracranial EEG (iEEG) findings (Halgren et al, 1998), topographic scalp ERP studies (Johnson, 1989b;Falkenstein et al, 1994), and lesion studies (Johnson, 1989a) also indicated different sources for the visual and auditory modality.…”
Section: P3b and Sensory Modalitycontrasting
confidence: 94%
“…However, the use of only few scalp electrodes without constraining the solution space by MRI and/or fMRI data likely explains both the differences among these studies and our partly diverging findings. Moores et al (2003) methodologically improved the ERP source-localization approach by using 124 electrodes and constraining the solution space by the individual brain anatomy. They identified source activity bilaterally in the intraparietal sulcus and superior parietal lobule (SPL), which partly conforms to our findings.…”
Section: Relationship To Previous Source Localization Studiesmentioning
confidence: 99%
“…According to the ICA concept, EEG channel activity is interpreted as a signal mixture of spatially distributed neuronal modules. 23,32,33 Following this line of reasoning, the present findings suggest that the cerebral control of the penile response is driven by several spatially distributed modules. ERP averaging likely filtered out spatiotemporal information, which in contrast was uncovered by means of ICA decomposition.…”
Section: Discussionsupporting
confidence: 63%
“…These different methods have provided evidence of the involvement of several areas in the generation of P3b: (1) the inferior parietal lobe and temporoparietal junction [Anderer et al, 2003;Menon et al, 1997;Mulert et al, 2004;Yamazaki et al, 2001]; (2) the superior and posterior parietal areas [Halgren et al, 1995;Linden, 2006;Moores et al, 2003]; (3) the cingulum [Linden, 2006;Mulert et al, 2004;Wang et al, 2005]; (4) the temporal lobe [Anderer et al, 2003;Hegerl and Frodl-Bauch, 1997;Mulert et al, 2004;Opitz et al, 1999;Tarkka and Stokic, 1998;Winterer et al, 2001]; and (5) the frontal and prefrontal areas [Anderer et al, 2003;Linden, 2006;Mulert et al, 2004;Smith et al, 1990;Yamazaki et al, 2001]. On the basis of intracranial recordings made during the presurgical investigation of epileptic patients, mesiotemporal structures (and particularly the hippocampus and amygdala) were initially proposed as P300 generators [Halgren et al, 1980;Mccarthy and Wood, 1987b;Mccarthy et al, 1989].…”
Section: Introductionmentioning
confidence: 99%